TOPOLOGY OPTIMIZATION FOR ADDITIVE MANUFACTURING - Kassym, Kazybek (Nazarbayev University School of Engineering and Digital Sciences, 2021)
The main aim of this project is to assess the use of topology optimization (TO) methods in additive manufacturing in conjunction with the effect of 3D-printing parameters on the resulting strength of the printed objects. The two most common topology optimization methods, i.e., Density and Level-Set, were used with the aim of minimizing the mass of a given prototype solid entity while maintaining, to the extent possible, its tensile strength. A family of designs was produced for different levels of retained mass. Specifically, topologically optimized designs were generated for mass levels ranging from 100% to 50% of the original entity’s mass with a 10% reduction step. These designs were experimentally assessed in conjunction with varying infill patterns and infill density 3D-printing parameters. The assessment was carried out systematically via tensile testing of 126 specimens and generation of the corresponding stress-strain graphs. In summary, the non-optimized entities and the 10%-mass-reduced designs produced practically identical results, whereas the 30% and 50%-mass-reduced ones exhibit slightly lower values for the max load at the break. Furthermore, the employed Density method seems to produce results that are better suited for 3D printing as it was computationally inexpensive, and it consistently generated designs that outperformed the ones generated by the employed Level-Set method. Regarding 3D-printing parameters, we can state that the ‘triangle’, ‘line’ and ‘grid’ patterns produce equal quality printouts. Finally, the lower value of infill density produced unexpected results and break points that could be possibly explained by the introduction of large gaps in the interior of the printed model. Further studies are needed to assess, qualitatively and quantitatively, the effect of infill density on the strength of printed objects.
Keywords: 3D; Research Subject Categories::TECHNOLOGY; 3D printer; topology optimization; TO; Type of access: Gated Access